Pengaruh Variasi Fraksi Volume Terhadap Kekuatan Tarik, Impact dan Rambat Bakar Komposit Serat Pisang Abaka - Risqi Romadhon; Deni Andriyansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the effect of variations in the volume fraction of abaca banana fiber (Musa textilis) on the mechanical properties and fire resistance of composites with a polyester resin matrix. The fibers were treated with an alkali solution of 5% KOH before being mixed into the resin with volume fractions of 10%:90%, 15%:85%, and 20%:80%. The tests included tensile testing (ASTM D-638), impact testing (ASTM A-370), flame spread testing (ASTM D-635), and macro photography. The tensile test results showed an increase in tension from 13.75 MPa at 10% fiber to 19.1 MPa at 20% fiber, accompanied by a decrease in strain and an increase in elastic modulus to 1.71 GPa. The impact test showed the highest impact energy absorption at 20% fiber content of 10.54 Joules with an impact value of 97.488 J/m². The macro photo results showed that more fibers increased the fiber-matrix interface bond, although voids were still found. In the flame spread test, the ignition time increased to 7.64 seconds and the flame spread rate decreased to 10.593 mm/minute at a fiber variation of 20%, due to the formation of an insulating char layer. Overall, the 20% abaca fiber volume fraction proved to provide the best mechanical properties and fire resistance, making it the recommended optimal composition for the development of environmentally friendly natural fiber composites.